Competition, Corporate Governance, and Regulation in Central Asia : Uzbekistan's Structural Reform Challenges - Broadman, Harry G. (World Bank, Washington, DC, 2015)
In Uzbekistan state enterprises are being changed into shareholding companies, and private enterprises account for 45 percent of all registered firms. But business decisions to set prices, output, and investment are often not market-based, nor wholly within the purview of businesses, especially those in commercial manufacturing and services. Lines of authority for corporate governance - from state enterprises to private enterprises - are ill-defined, so there is little discipline on corporate performance and little separation between government and business. Nascent frameworks have been created for competition policy (for firms in the commercial sector) and regulatory policy (governing utilities in the infrastructure monopoly sector). Bur implementation and enforcement have been hampered by old-style instruments (such as price controls0 rooted in central planning, by lack of a strong independent regulatory rule-making authority, by the limited understanding, of the basic concepts of competition and regulatory reform, and by weak institutional capabilities for analyzing market structure and business performance. Based on fieldwork in Uzbekistan, the author recommends: 1) Deepening senior policy officials' understanding of, and appreciation of the benefits from, enterprise competition and how it affects economic growth. 2) Reforming competition policy institutions and legal frameworks in line with the country's goal of strengthening structural reforms and improving macroeconomic policy. 3) Improving the ability of government and associated institutions to assess Uzbekistan's industrial market structure and the determinants of enterprise conduct and performance. 4) Making the authority responsible for competition and regulatory policymaking into an independent agency - a "champion" of competition - answerable directly to the prime minister. 5) Strengthening incentives and institutions for corporate governance and bringing them in line with international practice. 6) Subjecting infrastructure monopolies to systemic competitive restructuring and unbundling, where appropriate. For other utilities, de-politicize tariff setting and implementation of regulations; ensure that price, pro-competitive (creating a level playing field among users); and increase transparency and accountability to the public.